Current advances and prospects in NiO-based lithium-ion battery anodes. (October 2022) - Ata-ur-Rehman; Iftikhar, Muhammad; Latif, Salman; Jevtovic, Violeta; Ashraf, I.M.; El-Zahhar, Adel A.; Abdu Musad Saleh, Ebraheem; Mustansar Abbas, Syed
Graphical abstract: Abstract: The prevalent LIBs are becoming unsatisfactory in terms of their capacity to meet the growing demands of expanding battery industry so copious attempts have been made to introduce new anode materials for lithium-ion batteries (LIBs) to enhance their performance. In this thirst Ni-based anode materials with about double the theoretical capacity (718 mAhg −1 ) than the prevalent graphite (372 mAhg −1 ) anode, along with long cycle life, natural abundance and being environment friendly have been much explored with many attempts going on a toss-up base. This review focuses on various morphologies of NiO-based materials ranging from bare NiO, doped NiO hybrid oxides and composites with various types of carbonaceous materials that have been proved to accommodate advanced LIB applications. It has been found that the electrochemical properties of NiO-based anodes for LIBs is generally reliant on morphology, crystallinity, particle size, surface area and porosity. In comparison with pure NiO, the carbon-supported and metal oxide doped composite NiO structures present much higher specific capacities owing to the synergistic effect of all the components but the pulverization and capacity drainages due to multiple effects need to be explored in detail for the effectiveness of NiO as an electrode material in LIBS. A detailed script on morphology–performance have been highlighted with a special focus on the factors contributing to the capacity and possible solutions for future efficacy of NiO hybrid electrodes.